«Военные рассказы» М. Кузмина: Попытка реинтерпретации [Toward the Reinterpretation of Mikhail Kuzmin’s _War Stories_] - Pakhomova, Alexandra (Slavica Revalensia, 2021)
The article analyzes War Stories (Voennye rasskazy, 1915) by Mikhail Kuzmin and offers a new interpretation of the book’s pragmatics. Most students of War Stories have not treated this collection in much detail, mainly seeing it as Kuzmin’s unsuccessful attempt to become a part of the mainstream patriotic movement during WWI. Contrary to her predecessors, Alexandra Pakhomova argues this particular book has a definite and consciously motivated authorial strategy. What Kuzmin did in War Stories was an attempt to establish his new literary reputation, and also to create an entirely new genre of short fiction in Russian literature.